8th OpenSky Symposium 2020 2020
DOI: 10.3390/proceedings2020059007
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory Clustering within the Terminal Airspace Utilizing a Weighted Distance Function

Abstract: To support efforts to modernize aviation systems to be safer and more efficient, high-precision trajectory prediction and robust anomaly detection methods are required. The terminal airspace is identified as the most critical airspace for individual flight-level and system-level safety and efficiency. To support successful trajectory prediction and anomaly detection methods within the terminal airspace, accurate identification of air traffic flows is paramount. Typically, air traffic flows are identified utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…A trajectory clustering task is generally defined as a process partitioning a collection of trajectories into similar groups [109]. The trajectory clustering task, which is typically formulated as an unsupervised machine learning problem, has been widely used in various engineering areas such as civil and aerospace engineering.…”
Section: Flight Trajectory Clusteringmentioning
confidence: 99%
“…A trajectory clustering task is generally defined as a process partitioning a collection of trajectories into similar groups [109]. The trajectory clustering task, which is typically formulated as an unsupervised machine learning problem, has been widely used in various engineering areas such as civil and aerospace engineering.…”
Section: Flight Trajectory Clusteringmentioning
confidence: 99%
“…A good number of studies address the trajectory clustering in the TMA. In some cases, the goal is identification of the flows in the TMA (for example, [14]). In other cases, the goal is the trajectory prediction.…”
Section: Related Workmentioning
confidence: 99%
“…While real-time application is not the focus of this work, aviation organizations have set goals to ultimately deploy novel anomaly detection methods in real-time or near-realtime [6]. Corrado et al [48] proposed the utilization of a weighted Euclidean distance function to cluster trajectories and demonstrated that certain weighting schemes resulted in a more accurate clustering. The weighted Euclidean distance computation proceeds as:…”
Section: Spatial Anomaly Detectionmentioning
confidence: 99%
“…Clustering algorithms rely on the definition of a distance function. In previous work by the authors [48]), the effectiveness of a weighted Euclidean distance function to identify air traffic flows is demonstrated. The results indicated a more robust identification of outliers.…”
Section: Spatial Anomaly Detectionmentioning
confidence: 99%
See 1 more Smart Citation